Human papillomavirus testing for triage of women with low‐grade squamous intraepithelial lesions1. Issue 4 (3rd August 2012) - Cuzick, Jack; Thomas Cox, J.; Zhang, Guili; Einstein, Mark H.; Stoler, Mark; Trupin, Suzanne; Behrens, Catherine M.
Abstract Low‐grade squamous intraepithelial lesion (LSIL) is a common cytologic finding in cervical screening, yet only about 10–20% have significant histologic abnormalities and these are almost always positive for high‐risk human papillomavirus (hrHPV). This analysis aims to clarify the role of hrHPV DNA testing in the triage of women with LSIL cytology. In the ATHENA screening trial, we examined 1, 084 cases of LSIL, of which 925 had an evaluable biopsy, to determine the extent to which hrHPV testing can identify those patients who have precursor lesions in need of immediate clinical referral and those who have changes more likely to regress spontaneously. Overall, 71.2% of LSIL cases were hrHPV positive, but the prevalence was age dependent, with only 56.1% in women ≥40 years. Among women with LSIL, 11.6% (107/925) had a cervical intraepithelial neoplasia grade 2 or worse (CIN2+) histologic diagnosis and, of these, only nine were hrHPV negative. For CIN3+, 91.7% (44/48) of women with LSIL were hrHPV positive. The negative predictive value of hrHPV testing for CIN3+ in LSIL was 100% for women aged ≥40 years. Women who were HPV16 positive had a higher positive predictive value for CIN2+ (25.4%) than those who were positive for 12 other pooled hrHPV types (11.5%). Testing for hrHPV in women with LSIL is effective in identifying high‐grade cervical lesions, thereby avoiding unnecessary referrals to colposcopy and potential over‐treatment of non‐progressive lesions, especially for women aged ≥40 years.